THE INFLUENCE OF BUDGET PARTICIPATION ON MANAGERIAL PERFORMANCE WITH ORGANIZATIONAL COMMITMENT, LOCUS OF CONTROL AND DECENTRALIZATION AS MODERATING VARIABLES AT PT POS INDONESIA JAMBI CITY - Melli Ramadhia Rusfa; Yudi Yudi; Muhammad Gowon (Transpublika Publisher, 2024)
This research aims to determine the effect of budget participation on managerial performance with organizational commitment, locus of control and decentralization as moderating variables at PT. Pos Indonesia Jambi City. This research was conducted through a survey by distributing online questionnaires to the participants. A total of 67 employees from PT. Pos Indonesia Jambi City were selected as the sample for this study. The collected data was analyzed using a specific data analysis method. Prior to hypothesis testing, the classical assumptions were examined. The hypothesis testing was conducted using moderated regression analysis (MRA), including t-tests, F-tests, and coefficient of determination tests. The findings of this research indicate that budget participation has a significant impact on managerial performance. Furthermore, organizational commitment, locus of control, and decentralization collectively have a significant influence on the relationship between budget participation and managerial performance. However, individually, organizational commitment, locus of control, and decentralization do not have an effect on the relationship between budget participation and managerial performance.